2017
DOI: 10.1177/1010428317719578
|View full text |Cite
|
Sign up to set email alerts
|

XIAP 3′-untranslated region serves as a competitor for HMGA2 by arresting endogenous let-7a-5p in human hepatocellular carcinoma

Abstract: X-linked inhibitor of apoptosis protein functions as an intrinsic regulator of apoptosis by inhibition of caspase activity and possesses a pivotal role in human cancer development and progression. A growing body of literature has demonstrated that microRNAs lead to the degradation or translational repression of messenger RNAs by binding to the non-coding region of messenger RNA at the 3′-untranslated region. Here, we revealed that the expression of HMGA2 is upregulated with X-linked inhibitor of apoptosis prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Our results proposed combinations of let-7a-5p and miR-1246, let-7f-5p and miR-4532, miR-320c and let-7a-5p, miR-122-5p and let-7a-5p and the selected panel, namely, miR-320b/c and let-7a-5p, that showed the highest AUC of 0.9822. Of these three miRNAs, only let-7a-5p is supported by multiple studies indicating that let-7a-5p can modulate cell growth, migration and invasion, cell proliferation and apoptosis, and importantly, that it is associated with hepatis B and viral carcinogenesis, as indicated in Figure 4 [60][61][62][63][64]. In a Chinese cohort where 74.8% of patients were HBV positive, three serum-exosome-derived miRNAs (miR-122-5p, let-7d-5p and miR-425-5p) with an AUC of 0.905 were identified as promising biomarkers for identifying HCC patients [225].…”
Section: Discussionmentioning
confidence: 91%
“…Our results proposed combinations of let-7a-5p and miR-1246, let-7f-5p and miR-4532, miR-320c and let-7a-5p, miR-122-5p and let-7a-5p and the selected panel, namely, miR-320b/c and let-7a-5p, that showed the highest AUC of 0.9822. Of these three miRNAs, only let-7a-5p is supported by multiple studies indicating that let-7a-5p can modulate cell growth, migration and invasion, cell proliferation and apoptosis, and importantly, that it is associated with hepatis B and viral carcinogenesis, as indicated in Figure 4 [60][61][62][63][64]. In a Chinese cohort where 74.8% of patients were HBV positive, three serum-exosome-derived miRNAs (miR-122-5p, let-7d-5p and miR-425-5p) with an AUC of 0.905 were identified as promising biomarkers for identifying HCC patients [225].…”
Section: Discussionmentioning
confidence: 91%
“…Our study proved, for the first time, that HMGA2 , a target gene of let-7a-5p, was 3.19-fold upregulated in the SAT of morbidly obese Chinese women. In previous studies, HMGA2 was confirmed to be a target gene of let-7a-5p, and the expression of HMGA2 was upregulated by arresting endogenous let-7a-5p [59]. In addition, the transfection of let-7 into 3T3-L1 cells could lead to a >3-fold decreased expression of HMGA2 [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that overexpression of miRNA let-7a-5p can inhibit the expression of X-linked inhibitor of apoptosis protein (XIAP) and high mobility protein A2 (HMGA2), thereby inhibiting the development and proliferation of liver cancer. 19 Through further analysis of qRT-PCR, we found that there is a significant negative correlation between miRNA let-7a-5p and BZW2 mRNA expression. We speculate that the decrease in the expression of miRNA let-7a-5p may partly explain the mechanism of the up-regulation of BZW2 expression in liver cancer tissues.…”
Section: Introductionmentioning
confidence: 85%